Penerapan Pembelajaran Reflektif melalui Jurnal Belajar Matematika untuk Memperkuat Keterkaitan Antar Langkah dalam Pemecahan Masalah - Rachmat Imam Muslim; Utomo Utomo; Meilan Tri Wuryani; Ade Bagus Primadoni; Muhamad Akrom (Lembaga Bale Literasi, 2025)
The problem of interrelationships between steps in solving mathematical problems is still a challenge in learning at the elementary school level. Many students have not been able to formulate solutions logically and completely due to a lack of reflective awareness of their thinking process. This study aims to describe the process of implementing reflective learning through mathematics learning journals and to analyze its impact on the interrelationships between students' thinking steps in problem solving. The study used the Classroom Action Research (CAR) method which was carried out in two cycles on fifth grade elementary school students with a total of 26 students as subjects. The instruments used included observation sheets, interview guidelines, problem-solving tests, and reflective journal assessment rubrics. The results showed that the implementation of reflective journals gradually increased the clarity of the sequence of steps (from 60% to 75%), the rationale for strategies (35% to 60%), and the identification of difficulties (25% to 55%). The average problem-solving test score also increased from 68 to 82. These findings indicate that reflective learning through learning journals is effective in strengthening logical understanding between steps and encouraging students' metacognitive awareness in solving mathematical problems.